Metode Nominee Agreement Saham Pada Bidang Usaha Bersyarat di Indonesia - ivana, ivana (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
Legally, the concept of the nominee is recorded in the articles of association of a company as the actual owner before the law while the principal investor is the controller of the nominee so it is difficult to deny that this method is one way for principal investors to circumvent the provisions and restrictions given by the government for them to control a number of shares. So that in its existence this type of agreement still exists and develops in the legal ecosystem in Indonesia. This article aims to analyze the practice of investment using nominee agreement shares, especially in the field of conditional open business in Indonesia. Data is collected from literature sources and legal documentation. This research uses normative legal research methods to find the truth based on the logic of legal science from the normative side. The results of this study indicate that the restrictions imposed by the Indonesian government on investment by foreign parties are one of the backgrounds for the emergence of the Nominee concept in share ownership, which is widely known as nominee shareholders. This can be done and differentiated into two, namely nominee share arrangement and nominee agreement, but in Indonesia more use the practice of nominee share arrangement where the proof of this action can be said to be difficult.